Some Remarks on the Weak Interaction of Mean and Turbulent Fields of Temperature and Wind Velocity - Chakraborty, A.K.; Mazumdar, H.P.; Persen, L.N. (Engineering Transactions, 1985)
Some spectral characteristics of the kinetic energy spectrum E (x) corresponding to the case when interaction between the vorticities of the main and turbulent motions is weak and b = (du/dz)2 -ab(dT/dz) can be treated as a small nonzero parameter, are examined with the help of a perturbation method as an alternative approach.